2022
DOI: 10.3390/ijerph191912337
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics of Elite Male Bandy Players

Abstract: Physical characteristics of elite male bandy players have not been studied for the last 30 years. Therefore, the purpose of this study was to evaluate the physical characteristics of elite male bandy players with respect to playing positions. A cross-sectional study was performed that included 25 male bandy players from one of the highest-ranked bandy leagues in the world. Body weight, length, isometric mid-thigh pull, countermovement jump, squat jump, unilateral long jump, bilateral long jump, 15- and 30-m sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Moreover, there is only one study recently published that investigated physical characteristics (e.g., body mass and height, aerobic power, lower-body power and strength) of elite male bandy players across playing positions. In brief, Petré et al (2022) found only superior VO 2max in forwards compared to defenders, while there were no significant differences for any other measurements between playing positions. However, as in our sample of women, defenders in their study were heavier than forwards, even though the difference was not significant (86.5 ± 8.3 kg vs 83.1 ± 7.8 kg, respectively).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Moreover, there is only one study recently published that investigated physical characteristics (e.g., body mass and height, aerobic power, lower-body power and strength) of elite male bandy players across playing positions. In brief, Petré et al (2022) found only superior VO 2max in forwards compared to defenders, while there were no significant differences for any other measurements between playing positions. However, as in our sample of women, defenders in their study were heavier than forwards, even though the difference was not significant (86.5 ± 8.3 kg vs 83.1 ± 7.8 kg, respectively).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it is impossible to compare the anthropometrics and skating performance data from the current study to any previous research. However, the results can be compared to the findings of previous studies that investigated only elite male bandy players ( Blomqvist et al, 2018 ; Johansson et al, 2021 ; Persson et al, 2021 ; Petré et al, 2022 ). In general, both senior and junior female players from the current study were lighter and shorter (63.2 ± 7.4 kg and 1.67 ± 0.06 m) than the elite male bandy players from previous studies (82.8 ± 4.2 kg and 1.81 ± 0.04 m ( Johansson et al, 2021 ; Persson et al, 2021 ); (83.8 ± 7.6 and 182.4 ± 6.6; ( Petré et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations